Evaluation of the Success Criteria for Zirconia Dental Implants: A Four-Year Clinical and Radiological Study - Andrea Enrico Borgonovo; Rachele Censi; Virna Vavassori; Marcello Dolci; Josè Luis Calvo-Guirado; Rafael Arcesio Delgado Ruiz; Carlo Maiorana (Hindawi Limited, 2013)
Objectives. The aim was to evaluate survival and success rates, soft tissue health, and radiographic marginal bone loss (MBL) of zirconia implants placed in the esthetic and posterior areas of the jaws and in association with multiple or single implant restorations after at least 6 months of definitive restoration. Material and Methods. 35 one-piece zirconium implants were utilized for single or partially edentulous ridges rehabilitation. All implants received immediate temporary restorations and six months after surgery were definitively restored. Every 6 months after implant placement, a clinical-radiographic evaluation was performed. For each radiograph, the measurements of MBL were calculated. Results. The results showed that the mean MBL at 48-month followup was 1.631 mm. The mean MBL during the first year of loading was not more significant for implants placed in the first molar regions than for those positioned in other areas. Moreover, no differences in marginal bone level changes were revealed for multiple and single implants, whereas MBL in the first year was observed to be slightly greater for implants placed in the maxilla than for those placed in the mandible. Conclusion. Zirconia showed a good marginal bone preservation that could be correlated with one-piece morphology and characteristics of zirconia implants.